2022
DOI: 10.55414/ap.v41i1.957
|View full text |Cite
|
Sign up to set email alerts
|

La importancia de investigar la presentación de preguntas de elaboración para la facilitación de la comprensión del discurso: brechas en la investigación actual y futuras direcciones.

Abstract: La comprensión del discurso es central para la participación social y el desempeño en el ámbito educativo. Estudios previos sugieren que la realización de tareas de elaboración la facilitan, dado que promueven que los lectores se involucren con el texto, y lo procesen más profundamente. Entre ellas, las preguntas de elaboración (tales como: ‘Por qué la oración que leíste es cierta?’) tienen un rol destacado. Considerando la importancia de facilitar la comprensión de textos para el ámbito educativo, el objetivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
1
3
0
1
Order By: Relevance
“…These findings converge with studies that have indicated that discourse comprehension can promote the activation of intense emotions [74]. They also expand prior studies, given that they highlight that we can apply psycholinguistic knowledge to promote active learning from materials on social issues, such as GBV prevention [14,15,17]. Our findings also contribute to the promotion of the development and implementation of interventions that are evidence based.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These findings converge with studies that have indicated that discourse comprehension can promote the activation of intense emotions [74]. They also expand prior studies, given that they highlight that we can apply psycholinguistic knowledge to promote active learning from materials on social issues, such as GBV prevention [14,15,17]. Our findings also contribute to the promotion of the development and implementation of interventions that are evidence based.…”
Section: Discussionsupporting
confidence: 89%
“…Even though these interventions have been successful in promoting the identification of early signs of violence and beliefs that justify it, both in Ecuador and Argentina they have not focused on the facilitation of participants' learning from psychoeducation materials on GBV [14,17,55]. This gap is important, given that these materials are key to promote that participants learn about how to identify whether themselves, their relatives or friends are in a in relationship that could involve GBV, and how to intervene early [51] The development of psychoeducational materials that facilitate learning about the prevention of GBV can be challenging, because they need to be based on effective prior research [17,56]. In relation to this, prior studies on the facilitation of learning from narrative and expository discourse have not tended to focus on spontaneously produced materials on social issues such as GBV, but rather on research-created materials on other topics [14,15,17,57].…”
Section: How Can the Prevention Of Gbv Be Promoted?mentioning
confidence: 99%
See 2 more Smart Citations
“…Estas investigaciones destacan la importancia de que nuevos estudios continúen examinando la comprensión de otro tipo de materiales de discurso hablado espontáneo (tales como clases grabadas), y otras modalidades (hablada-escrita combinada, hablada-hablada). También cabe destacar que los materiales presentados por los estudios no han tendido a tratar acerca de problemáticas sociales actuales (Pispira & Cevasco, 2022). En relación con esto, en nuestro laboratorio nos encontramos examinando el rol de promover el establecimiento de conexiones causales entre enunciados, a través de la realización de tareas de toma de notas, en la comprensión de materiales acerca de la implementación de la Educación Sexual Integral en las escuelas por parte de estudiantes universitarios argentinos.…”
Section: Brechas En La Investigación Acerca De Este Modelo Y Futuras ...unclassified